PENINGKATAN LAYANAN DALAM MENINGKATKAN MINAT BELI KONSUMEN DI IZZI BAKERY - Muharroroh Lihidmatiddinil Qowim (IZZI: Jurnal Ekonomi Islam, 2023)
This study aims to determine the effect of service quality on consumer buying interest at Izzi Bakery and identify other factors that influence consumer buying interest. This type of research uses qualitative methods. The data collection techniques used were observation, interviews, and data from documentation. The data analysis technique used secondary data, namely, interviews and direct observation. Based on the results of the interviews obtained indicate that the quality of service is very influential on consumer buying interest and Izzi Bakery has provided good service quality in accordance with the existing theory. Service quality has a positive and significant impact on the resilience of a business to continue to exist and increase the number of consumers every day to attract consumer buying interest.